2014
DOI: 10.1177/1087054714560822
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction and Functional Impairment Associated With Sluggish Cognitive Tempo in Emerging Adulthood

Abstract: SCT is a clinical construct worthy of additional study, particularly among college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
102
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(124 citation statements)
references
References 34 publications
14
102
4
4
Order By: Relevance
“…A similar pattern was reported by a smaller number of studies that examined the relation between SCT and impairment in adults 16,19,43,46,51,52 . These studies found significant correlations between SCT and global impairment ( r =0.52), academic impairment ( r =0.45), and social impairment ( r =0.37), with correlations that were similar in magnitude to the results obtained in studies of children and adolescents.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…A similar pattern was reported by a smaller number of studies that examined the relation between SCT and impairment in adults 16,19,43,46,51,52 . These studies found significant correlations between SCT and global impairment ( r =0.52), academic impairment ( r =0.45), and social impairment ( r =0.37), with correlations that were similar in magnitude to the results obtained in studies of children and adolescents.…”
Section: Resultssupporting
confidence: 83%
“…In contrast, three studies with adults have shown SCT to be significantly correlated with executive functioning in daily life as assessed with self-report rating scales 16,43,52 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Both studies showed that SCT contributed unique variance to EF subscales of Self-Organization/ Problem Solving and Emotional Self-Regulation on the Barkley Deficits in Executive Function Scale (BDEFS; Jarrett et al, 2014), whereas ADHD inattentive symptoms more strongly predicted self-management to time. SCT contributed to the Total EF score more than (Wood et al, 2014) or equally (Jarrett et al, 2014) with ADHD-I. Jarrett et al (2014) also tested participants on visual working memory, set-shifting, and attention and found no relationship between these neuropsychological test results and either SCT or ADHD symptoms.…”
Section: Sct In Adultsmentioning
confidence: 93%